PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT RAPALA VMC BATAM - Butar-butar, Pininta Juliana; Tampubolon, Rikson Pandapotan (SCIENTIA JOURNAL, 2019)
In this era globalization the level of, company competition geeting tougher. To be able to survive and develop into a superior company, it must have strength to stay be able keep move forward and face challenges. The purpose of this research is to explain the effect of work discipline and work motivation on employed performances on PT Rapala VMC Batam. The sample that use on this research is 128 responden. The thecnic of collecting data that the researcher used on this research is questionnaire. The technic of data analysis on this research is multiple linier regression analysis. Based on the result of analysis by the researcher on this research, it was found that work dicipline has positive effect and significant influence to the employed performances of the employed on PT Rapala VMC Batam. The work motivation has positive effect and significant influence to the employed performance of the employed on PT Rapala VMC Batam. This research proves that work dicipline and work motivation able to increase the performance of the employed on PT Rapala VMC Batam.